2010
DOI: 10.1128/aem.02323-09
|View full text |Cite
|
Sign up to set email alerts
|

Functional Genomic Study of Exogenous n -Butanol Stress in Escherichia coli

Abstract: n-Butanol has been proposed as an alternative biofuel to ethanol, and several industrially used microbes, including Escherichia coli, have been engineered to produce it. Unfortunately, n-butanol is more toxic than ethanol to these organisms. To understand the basis for its toxicity, cell-wide studies were conducted at the transcript, protein, and metabolite levels to obtain a global view of the n-butanol stress response. Analysis of the data indicates that n-butanol stress has components common to other stress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
258
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 215 publications
(279 citation statements)
references
References 51 publications
16
258
1
Order By: Relevance
“…Challenge of E. coli DH1 with n-butanol during mid-log growth transiently activated yqhD; 6-fold induction was observed at 30 minutes, with the 80 and 195 minute samples showing less than a 2-fold change relative to the control sample (Rutherford et al 2010). …”
Section: E Coli Omics Data (University Of Oklahoma Gene Expression Dmentioning
confidence: 98%
See 1 more Smart Citation
“…Challenge of E. coli DH1 with n-butanol during mid-log growth transiently activated yqhD; 6-fold induction was observed at 30 minutes, with the 80 and 195 minute samples showing less than a 2-fold change relative to the control sample (Rutherford et al 2010). …”
Section: E Coli Omics Data (University Of Oklahoma Gene Expression Dmentioning
confidence: 98%
“…Additionally, a BW25113 yqhD deletion mutant showed increased sensitivity to butanol challenge (Rutherford et al 2010). Given that superoxide dismutase sodA was also activated, the authors attributed this yqhD activation to oxidative stress.…”
Section: E Coli Omics Data (University Of Oklahoma Gene Expression Dmentioning
confidence: 99%
“…Downregulation of methionine synthesis genes was also observed in E. coli under butanol stress. 15 As methionine is the first amino acid residue in any protein, E. coli could control the global protein expression by depressing methionine biosynthesis under stress conditions.…”
Section: Proteins Involved In Amino Acids Metabolismmentioning
confidence: 99%
“…One of such studies, performed on the natural producer C. butyricum growing on glycerol, proposed that the inhibitory effect of this compound was similar to that produced by other diols, including membrane destabilization (49). Proteomic studies performed in E. coli strains accumulating ethanol and butanol have reported an increase in the content of HSPs (35,50), while the accumulation of 1,3-PDO in C. butyricum was also observed to trigger the synthesis of HSPs in a fashion similar to that observed in solvent-producing bacteria (51). Analysis of the genetic basis for tolerance to biofuels and other chemicals in several bacteria has revealed that it is a complex phenomenon, in which many different aspects and genes are involved, obviously including HSPs (52,53).…”
Section: Discussionmentioning
confidence: 99%